Acute appendicitis in a 14-year-old boy with familial Mediterranean fever - Yoshihiko Sakurai; Takaaki Murata; Hirohisa Hirata; Takeshi Morita (Elsevier, 2015)
Familial Mediterranean fever (FMF) is one manifestation of a heritable periodic fever syndrome that is characterized by recurrent attacks of febrile polyserositis, most frequently peritonitis. An FMF abdominal attack is often misdiagnosed as acute appendicitis, a more common cause of an acute abdomen. We report a 14-year-old boy with FMF who developed acute appendicitis during his follow-up. The patient had a several-year history of abdominal pain episodes, and was initially admitted for an acute abdominal attack. The attack resolved over three days, following administration of intravenous fluids, alone. Upon admission, serology revealed elevated serum levels of amyloid A. An analysis of the MEFV gene revealed compound heterozygous Glu148Gln/Ser503Cys, resulting in an FMF diagnosis. Seven months after discharge, the patient was re-admitted with an acute abdomen. Following ultrasonographically diagnosed appendicitis, an appendectomy was performed, and acute phlegmonous appendicitis was confirmed, based on the pathologic examination of the resected specimen. The present case suggests that upon examining an FMF patient with abdominal pain, appendicitis should not be arbitrarily discounted from the differential diagnosis.